Effectiveness Of Incubators On Physiological Stability Of Premature Babies - Astin Nur Hanifah; Wahyuni Anwar; Rezqiqah Aulia Rahmat; Tenny Tarnoto (International Journal of Health Sciences, 2026)
Premature infants are at high risk of experiencing physiological instability due to organ immaturity, especially in the regulation of body temperature, respiration, and the cardiovascular system. One of the main interventions in the care of premature infants is the use of an incubator. This study aims to determine the effectiveness of incubator use on the physiological stability of premature infants. The research method used was a quantitative study with an analytical observational design. The subjects were premature infants treated in the perinatology ward. The physiological parameters observed included body temperature, respiratory rate, and heart rate. The results showed that the use of an incubator significantly helped maintain the physiological stability of premature infants. Thus, an incubator is an effective and essential tool in the care of premature infants to improve physiological stability and prevent further complications.